Analisa botol plastik yang dapat digunakan sebagai bata penyusun bangunan dengan metode elemen hingga - Muhammad Ikhsan; Muhammad Iqbal Mudzakky; Daniel Dwi Putra Wibowo (Badan Kerja Sama Teknik Mesin Indonesia, 2019)
In this paper, writers create a new design of reusable plastic bottle, which can reuse as building bricks called Rubicks v. 2.1 with some upgrade of the design that can reinforce static strength when the body of bottle applied by a force. The purpose of this research are to find and to analyze the magnitude of force that can make the design of bottle will be fail or damage. The method that used in this paper is Finite Element Method (FEM). In this paper, the bottle given ten of variation magnitude of forces from 200 N to 2000 N. The result and analyze that the lowest total deformation value is 0.22 mm and the highest total deformation value is 2.25 mm. For Maximum Shear Stress, the lowest maximum shear stress is when the bottle applied 200 N each is 3.66 MPa. Meanwhile, the highest maximum shear stress is when the bottle is applied 2000 N each is 36.65 MPa. The most effective of safety factor is chosen when the bottle have a value of safety factor equal or more than 1. The magnitude of force that can applied on the Rubicks v. 2.1 plastic bottle design is 1700 N.